(untitled) (Research, Society and Development, 2022)
By computer simulations, the behavior of meteoroids when entering the Earth’s atmosphere is studied. Given the initial mass and velocity parameters, the Modified Euler Integration numerical method is applied to solve the equations that describe the behavior of falling meteoroids. The numerical results obtained through arbitrary values inserted in the simulation showed good agreement when compared with the observables selected from the International Astronomical Union (IAU) database, but they show that improvements in accuracy can be made in future versions of the algorithm.